A Diagnostic Assistance Program - Bonner, R. E.; Evangelisti, C. J.; Steinbeck, H. D.; Cohen, L. (Methods of Information in Medicine, 1966)
A doctor must determine the specific diseases in a patient by judgment based on observation of any availble number of findings. Such, diagnoses can be assisted materially by computers through statistical analysis. Far more than statistics is involved; the mass of information in textbooks and in the minds of specialists is at .the heart of a successful diagnosis.Diagnostic assistance can be obtained by encoding the disease process itself. Then, all available known signs and symptoms of a disease and related conditions as observed by the physician are encoded for entry into a computer. Here the data is evaluated, and an output report is printed to show the effective relationship between the physician’s findings and the specific diseases.. When the result is inconclusive, new findings are obtained and entered into the computer. This process is repeated until satisfactory results axe obtained.The paper includes an example of diagnostic support by a computer, together with an illustration of the method used for developing the program.